2014
DOI: 10.1158/1078-0432.ccr-13-1271
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressive Effects of Bromodomain-Containing Protein 7 (BRD7) in Epithelial Ovarian Carcinoma

Abstract: Purpose: Bromodomain-containing protein 7 (BRD7), which is a subunit of SWI/SNF complex, has been recently suggested as a novel tumor suppressor in several cancers. In this study, we investigated the tumor suppressive effect of BRD7 in epithelial ovarian cancer.Experimental Design: We analyzed the expression of BRD7 in human ovarian tissues with real-time PCR. To investigate the functional role of BRD7, we transfected ovarian cancer cells (A2780 and SKOV3) with BRD7 plasmid and checked the cell viability, apop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 36 publications
0
65
0
Order By: Relevance
“…Accumulating evidence demonstrates that inactivation of the BRD7 gene contributes to the development of many human cancers by transcriptional dysregulation [1,2,[6][7][8][9][10][11][12][13]. BRD7 regulates signaling pathways that involve cell growth, apoptosis, cell cycle, and mobility [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence demonstrates that inactivation of the BRD7 gene contributes to the development of many human cancers by transcriptional dysregulation [1,2,[6][7][8][9][10][11][12][13]. BRD7 regulates signaling pathways that involve cell growth, apoptosis, cell cycle, and mobility [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that BRD7 was also down-regulated in multiple types of human cancer, including breast [6], prostate [7], endometrial [8], colorectal [9], ovarian [10], and pancreas cancer [11], glioma [12], and osteosarcoma [13]. BRD7 can inhibit cell growth through multiple mechanisms, including cell cycle arrest and apoptosis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that BRD7 was mostly located in the nucleus and regulated chromatin remodeling[1517]. More importantly, increasing evidences showed that BRD7 were downregulated in many cancers such as epithelial ovarian carcinoma, breast cancer, nasopharyngeal cancer and colorectal carcinoma [1821]. For example, Hu et al showed that BRD7 acted as a tumor suppressor in osteosarcoma, and knockdown of BRD7 increased colony formation, tumor growth and cell proliferation of osteosarcoma[22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hu et al showed that BRD7 acted as a tumor suppressor in osteosarcoma, and knockdown of BRD7 increased colony formation, tumor growth and cell proliferation of osteosarcoma[22]. Park et al demonstrated that overexpression of BRD7 inhibited ovarian cancer cells invasion, apoptosis and viability[18]. However, the role of BRD7 in lung adenocarcinoma is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…akt activation partially blocked mir-410-induced cell proliferation 184 . Brd7 is down-regulated in various malignancies [185][186][187] . However chen and Yu found that Brd7 expression was significantly higher in Nsclc tissues compared to normal lung tissue and also in an Nsclc lymph node metastasis group than that in the non-lymph node metastasis group 188 .…”
Section: Mirna Involved In Bone Metastasismentioning
confidence: 99%